Czy pedagogika polska ma swoje wielkie pytania? - Kwieciński, Zbigniew (Studia Edukacyjne, 2018)
The sources of the great questions of Polish pedagogy originate in the canon of eminent pedagogues of the interwar period, in the development blocks of our collective consciousness, in the dynamic cultural and developmental transformations on a global scale, and in the strong connections of pedagogy with its fundamental sciences.